Local inflammatory response to suture material in surgical practice: experimental data - T. N. Akentyeva; D. K. Shishkova; A. Yu. Burago; Yu. A. Kudryavtseva (Вестник трансплантологии и искусственных органов)
Objective: to study the effect of various types of suture materials, potentially suitable for cardiovascular surgery, on experimental surgical outcomes. Materials and methods. Polypropylene sutures (Prolene 6/0), titanium nickelide (TiNi) sutures (6/0) and absorbable polydioxanone sutures (Monoplus 6/0) were used in the study. Male Wistar rats were used for in vivo studies. The effect of suture materials on abdominal adhesions was studied. In vivo calcification process was examined, and response of blood components in contact with suture materials was also assessed in vitro. Results. There is a negative inflammatory response to suture materials. The severity of this response depended on the type of material used. Polypropylene sutures demonstrated the most severe inflammatory response provoking massive adhesion formation. In addition, large calcium deposits were found both in the suture area and in the thickness of the biomaterial, stitched with prolene and implanted subcutaneously in the rats. Titanium nickelide sutures showed high hemocompatibility and biocompatibility. The Monoplus sutures caused minimal inflammatory response and provoked calcification of the biomaterial to a lesser degree. Conclusion. The suture material could have significant effects on surgical outcomes and could cause postoperative complications.